'Little prisons': Revisiting trajectories and carcerality in a Danish asylum camp. Issue 1 (March 2022) - Jakobsen, Cecilie Odgaard
This article, closely grounded in empirical examples from an ethnographic fieldwork, draws attention to trajectories as an integral part of how carcerality amongst men seeking asylum in Denmark is experienced and navigated. By expanding on 'trajectory approach' to also explore how trajectories can be 'revisited', understood here as a 'return to' in person but most importantly in conversation, the author dives into an example of an interlocutor's stories of Bosnia, revisited from a camp in Denmark. It is argued, through this example, that the contrast between 'being in the camp' and the trajectory leading to the camp, offers up new insights on how everyday life in the camp is experienced and talked about as carceral.